Elastic compressible bismuth telluride composite thermoelectric material and preparation method and application thereof

By designing a mixture including bismuth telluride powder, graphene, pore-forming agent and polyurethane prepolymer, and using a multi-step treatment method, an elastic compressible bismuth telluride composite thermoelectric material with good thermoelectric properties and compression properties is solved, the application limitation of traditional bismuth telluride-based thermoelectric materials in the fields of flexible electronics and wearable devices is solved.

CN119604178AActive Publication Date: 2025-03-11NANKAI UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510147846.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-11
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

Traditional bismuth telluride-based thermoelectric materials limit their application in the fields of flexible electronics and wearable devices due to their rigidity and brittleness. At the same time, their preparation process is complex and costly.

Method used

通过将碲化铋粉体、石墨烯、造孔剂和聚氨酯预聚体混合均匀,并在模具中压制紧实固化,随后在水中除去氯化钠,进行高温处理以除去聚氨酯,最后在正己烷稀释的Ecoflex溶液中浸泡以填充孔隙,最终得到弹性可压缩碲化铋复合热电材料。

Benefits of technology

A high-performance elastic compressible thermoelectric material has good thermoelectric properties and compression properties, and is suitable for low-grade thermal energy collection, temperature monitoring and wearable electronics fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604178A_ABST
    Figure CN119604178A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermoelectric materials, and discloses an elastic compressible bismuth telluride composite thermoelectric material and a preparation method and application thereof, and the preparation method comprises the steps: uniformly mixing bismuth telluride powder, graphene, a pore forming agent and a polyurethane prepolymer, and compacting in a mold for curing; then soaking in water to remove sodium chloride; performing high-temperature treatment in a protective atmosphere to remove polyurethane to obtain a porous sample; and immersing the porous sample in an Ecoflex solution diluted by normal hexane, and curing in a drying oven to finally obtain the elastic compressible bismuth telluride composite thermoelectric material. The preparation process is simple, and the prepared elastic bismuth telluride composite thermoelectric material has good thermoelectric performance and compressibility, and has wide application prospects in the fields of flexible thermoelectricity, heat energy collection and wearing as a thermoelectric material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoelectric materials, and in particular to an elastically compressible bismuth telluride composite thermoelectric material and a preparation method and application thereof. Background Art

[0002] As an innovative material that can directly convert thermal energy into electrical energy, thermoelectric materials provide a new way to collect and utilize thermal energy. However, the rigidity and brittleness of traditional inorganic semiconductor thermoelectric materials limit their wide application in practical applications, making it difficult to effectively collect many low-grade thermal energies. In view of this, it is particularly important to develop flexible thermoelectric materials, which can not only broaden the application scope of thermoelectric materials, but also realize the innovation of flexible wearable devices, so as to more effectively collect low-grade thermal energy from the human body and daily life. Bismuth telluride is currently the only semiconductor thermoelectric material that has achieved commercial application. It has good thermoelectric properties and is widely used in thermoelectric power generation and thermoelectric refrigeration. However, traditional bismuth telluride-based thermoelectric materials and devices usually require high-temperature synthesis experimental equipment, plasma activated sintering equipment, grinding and polishing equipment, etc. during the preparation process, resulting in complicated and cumbersome preparation process and high cost. More importantly, due to its high rigidity and poor flexibility, the application of bismuth telluride in the field of flexible electronics and wearable devices is limited. Based on the above considerations, it is of great significance to design and prepare high-performance flexible bismuth telluride-based thermoelectric materials, which will promote their broad application prospects in the fields of flexible inorganic thermoelectrics, self-powered sensor monitoring, and wearable devices. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing a high-performance elastically compressible bismuth telluride composite thermoelectric material, so that the obtained thermoelectric material can obtain good thermoelectric performance and compression performance through design and regulation.

[0004] To achieve the above object, the present invention provides a method for preparing an elastically compressible bismuth telluride composite thermoelectric material, which comprises the following steps:

[0005] 1) Mix bismuth telluride powder, graphene, pore former and polyurethane prepolymer evenly, and compact them in a mold for curing;

[0006] Wherein: based on the mass of 1 g of polyurethane prepolymer, the mass of bismuth telluride powder is 0.5-10 g, the mass of pore-forming agent is 2-15 g, and the mass of graphene is 10-100 mg; the pore-forming agent is one or more of sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate;

[0007] 2) soaking the sample obtained by curing in step 1) in water to remove sodium chloride, drying it, and then subjecting it to high temperature treatment at 400-560° C. in a protective atmosphere to remove polyurethane, thereby obtaining a porous sample;

[0008] 3) The porous sample in step 2) is immersed in an Ecoflex solution diluted with n-hexane at a temperature of -10 to 5 °C, so that Ecoflex completely fills the pores of the sample. The sample is then taken out and placed in an oven for curing, and finally an elastically compressible bismuth telluride composite thermoelectric material is obtained.

[0009] As a further preferred technical solution of the present invention, the polyurethane type corresponding to the polyurethane prepolymer is one or a mixture of Clearflex PU95, Clearflex PU30, Clearflex PU60, and Clearflex PU200.

[0010] As a further preferred technical solution of the present invention, in step 1), based on the mass of 1 g of the polyurethane prepolymer, the corresponding mass of the bismuth telluride powder is 5-8 g.

[0011] As a further preferred technical solution of the present invention, in step 1), the curing temperature is 60-80°C and the curing time is 8-12 h.

[0012] As a further preferred technical solution of the present invention, in step 2), the temperature for soaking the sample to remove sodium chloride is 80-100°C, and the soaking time is 24-48 h; and / or, the drying temperature for drying is 60-80°C, and the time is 2-4 h; and / or, the high temperature treatment time is 2-6 h.

[0013] As a further preferred technical solution of the present invention, in step 3), the porous sample is immersed in the Ecoflex solution diluted with n-hexane for 8-12 h.

[0014] As a further preferred technical solution of the present invention, in step 3), the curing temperature is 60-80°C and the curing time is 0.5-2 h.

[0015] As a further preferred technical solution of the present invention, in the Ecoflex solution, the mass ratio of n-hexane to Ecoflex prepolymer is 1:1 to 1:2.

[0016] According to another aspect of the present invention, the present invention also provides a bismuth telluride composite thermoelectric material, which is prepared by the above method.

[0017] According to another aspect of the present invention, the present invention also provides an application of a bismuth telluride composite thermoelectric material as a thermoelectric material, specifically, it can be applied to the fields of sensor monitoring and flexible wearables.

[0018] The preparation method of the elastically compressible bismuth telluride composite thermoelectric material of the present invention adopts the above technical scheme, which can achieve the following beneficial effects:

[0019] (1) The preparation method of the present invention is simple and easy to implement, and has the potential for mass production;

[0020] (2) The elastically compressible bismuth telluride composite thermoelectric material of the present invention has good thermoelectric properties and compression properties;

[0021] (3) The present invention can prepare high-performance thermoelectric devices based on elastically compressible bismuth telluride composite thermoelectric materials, which have good application prospects in the fields of low-grade thermal energy collection, temperature monitoring, and wearable electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0023] Figure 1 The present invention is a flow chart of preparing an elastically compressible bismuth telluride composite thermoelectric material using bismuth telluride powder, graphene, sodium chloride and polyurethane;

[0024] Figure 2 The microstructure (SEM photo) and the distribution diagram of Bi, Sb and Te elements of the porous bismuth telluride composite material in Example 1;

[0025] Figure 3 This is an optical photograph of the elastically compressible bismuth telluride composite thermoelectric material in Example 1;

[0026] Figure 4 is the Seebeck coefficient of the high-performance porous bismuth telluride composite thermoelectric material after high-temperature treatment in Example 1 before and after immersion in Ecoflex;

[0027] Figure 5 The test results of the elastically compressible bismuth telluride composite thermoelectric material in Example 1 include stress-strain curves at different compression degrees (A) and the Seebeck coefficient after 1000 cycles of compression at 20% strain (B);

[0028] Figure 6 This is a test of the small temperature change response of the elastically compressible bismuth telluride composite thermoelectric material in Example 1;

[0029] Figure 7 The photos are of porous bismuth telluride composite thermoelectric materials obtained with different bismuth telluride contents in Examples 1 to 5;

[0030] Figure 8 is the Seebeck coefficient of the elastically compressible bismuth telluride composite thermoelectric material obtained under different high temperature treatments in Examples 6 and 7.

[0031] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0033] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0034] The bismuth telluride (Bi2Te3) used in the following examples was purchased from Zhongnuo New Materials (Beijing) Technology Co., Ltd., graphene was purchased from Sichuan Kenye Technology Development Co., Ltd., polyurethane (Clearflex-95) was purchased from Shanghai Zhixin Technology Co., Ltd., sodium chloride particles were purchased from China Salt Shanghai Salt Co., Ltd., and Ecoflex-0030 was purchased from SMOOTH-ON, USA.

[0035] The test method involved in the following embodiments: The Seebeck coefficient of the thermoelectric composite material is tested using a self-built test device. A low-voltage power supply, a commercial Peltier heating module, and TEC Service software are used to control the temperature (temperature difference) at the upper and lower ends of the thermoelectric device, and a Keithley 2450 data acquisition system is used to measure the open circuit voltage at both ends of the thermoelectric device, and the Seebeck coefficient is calculated. For the thermoelectric composite material designed in the embodiment of the present invention, taking a cylindrical structure as an example, the compression strain test of the bismuth telluride composite thermoelectric material is realized by a universal testing machine test system, and is connected to the Keithley 2450 system to record all electrical signals in real time.

[0036] Example 1

[0037] The preparation method of the elastically compressible bismuth telluride thermoelectric material and device of the present invention is as follows:

[0038] (1) Pour commercial p-type bismuth telluride powder (5 g), graphene (30 mg), sodium chloride particles (9 g), and polyurethane (Clearflex PU95) precursor component A (0.4 g) and precursor component B (0.6 g) into a cylindrical mold, stir and mix thoroughly, then press the mixture tightly and take it out (diameter 16 mm, height 16 mm) to obtain an uncured bismuth telluride composite material;

[0039] (2) placing the uncured bismuth telluride composite material in step (1) in an oven at 60°C for 12 hours, taking it out after curing, and then soaking it in hot water at 80°C for 48 hours to remove salt;

[0040] (3) placing the desalted bismuth telluride composite material in step (2) in an oven for drying again at a temperature of 60°C for 4 hours;

[0041] (4) subjecting the bismuth telluride composite material in step (3) to high temperature treatment, maintaining the temperature at 560°C for 3 h, with a heating rate of 4.5°C / min, and taking it out after the reaction is completed to obtain a porous bismuth telluride composite material;

[0042] (5) The porous bismuth telluride composite material obtained in step (4) is immersed in an Ecoflex-0030 solution diluted with n-hexane (2.5 g) (the mass ratio of n-hexane to Ecoflex prepolymer is 1:2), and placed in a refrigerator (temperature of -10~5°C) to prevent Ecoflex from curing at room temperature. After Ecoflex completely enters the pores of the porous bismuth telluride, the excess Ecoflex on the surface is removed and placed in an oven for curing again. The curing temperature is 60°C and the curing time is 1 h, thereby finally obtaining a high-performance elastic compressible bismuth telluride composite thermoelectric material.

[0043] Figure 1 The flow chart of preparing compressible bismuth telluride thermoelectric composite material using commercial p-type bismuth telluride powder (Bi2Te3), high graphene, polyurethane (PU) and sodium chloride (NaCl) in Example 1 is shown, including the main steps of curing, soaking, high-temperature sintering and resin dipping.

[0044] Figure 2 The microstructure and EDS element distribution diagram of the porous bismuth telluride composite material in Example 1 show that the material has a porous structure and the elements are evenly distributed.

[0045] Figure 3 This is an optical photograph of the elastically compressible bismuth telluride composite thermoelectric material after being immersed in Ecoflex glue in Example 1, showing the good compressibility and resilience of the porous bismuth telluride thermoelectric composite material after being immersed in glue. Specifically, when compressed by hand, it can be seen that the height before and after compression is almost unchanged, indicating good resilience.

[0046] Figure 4 The Seebeck coefficient test results of the high-performance porous bismuth telluride composite thermoelectric material before and after dipping in the glue in Example 1 (Vt diagram). The Seebeck coefficient before dipping in Ecoflex glue is 206.22 µV / K ( Figure 4 A), the Seebeck coefficient after dipping is 195.87µV / K ( Figure 4B). Before dipping, porous bismuth telluride is incompressible and can be easily crushed by pressing hard. After dipping, Ecoflex enters the pores of bismuth telluride and plays a supporting role. Since Ecoflex wraps up a small part of bismuth telluride, the Seebeck coefficient will be slightly reduced. In addition, compression testing will destroy the three-dimensional network structure of bismuth telluride, but the degree of damage is small, which will also cause the Seebeck coefficient to decrease slightly.

[0047] Figure 5 The mechanical properties of the elastically compressible bismuth telluride composite thermoelectric material under different compression strains and the thermoelectric properties under compression cycles in Example 1 show that the bismuth telluride composite thermoelectric material maintains good resilience under 10%, 20% and 30% compression tests using a universal testing machine, and no strain hysteresis behavior occurs ( Figure 5 A). After 1000 cycles of 20% compressive strain, the Seebeck coefficient only dropped from 197.37 µV / K to 186.32 µV / K, showing good thermoelectric stability ( Figure 5 B).

[0048] Figure 6 This is a test of the micro-temperature response of the elastically compressible bismuth telluride composite thermoelectric material in Example 1; Figure 6 A is a test diagram, using two commercial Peltier plates (which can achieve heating or cooling functions), one on top and one on the bottom. The upper one keeps the temperature constant, fixed at 20°C here, and the lower heating plate changes from 20°C to 20.05°C, 20.10°C, 20.15°C, and 20.20°C in sequence, with corresponding temperature differences of 0.05, 0.10, 0.15, and 0.2 K, respectively. The upper and lower electrodes of bismuth telluride are connected to the test instrument Keithley2450, and the voltage changes are recorded. The test data is shown in Figure 6 B. The test results show that the composite thermoelectric material can change the thermoelectric signal regularly under the change of small temperature difference, and the minimum monitored temperature difference can reach 0.05 K. The small temperature response test is often used in wearable electronic devices, such as monitoring the temperature change of human body; it is also often used in the field of artificial intelligence. For example, temperature monitoring is one of the most basic functions of bionic robots and can be used to identify the external temperature and the temperature of an object. At present, most temperature sensors have a resolution greater than 0.1 K, and very few can reach 0.05 K. The present invention can reach 0.05 K, indicating that it has excellent temperature monitoring capabilities.

[0049] Embodiment 2-5

[0050] Five groups of embodiments are provided to prepare elastically compressible bismuth telluride composite thermoelectric materials respectively, and the specific methods are as follows:

[0051] The amount of p-type bismuth telluride powder in step (1) in Example 1 was changed to 1 g, 2 g, 3 g, 4 g, and 10 g, respectively, and the remaining steps remained the same as in Example 1.

[0052] By adjusting the bismuth telluride content, the morphology of the obtained thermoelectric materials changes when the amount of p-type bismuth telluride powder is 1~5 g. Figure 7 As shown, it can be seen that only when the mass of bismuth telluride is greater than 4 g, the prepared thermoelectric material can maintain the same size and morphology as the initial after sintering. Among them, when the bismuth telluride content is small (1~4 g), the prepared bismuth telluride composite thermoelectric material will collapse after high temperature treatment, and the thermoelectric performance is relatively small. The specific test results are as follows (the following results are all without dipping):

[0053] At 1 g bismuth telluride content, the Seebeck coefficient of the corresponding composite thermoelectric material is 130 μV / K;

[0054] At 2 g bismuth telluride content, the Seebeck coefficient of the corresponding composite thermoelectric material is 150 μV / K;

[0055] At 3 g bismuth telluride content, the Seebeck coefficient of the corresponding composite thermoelectric material is 170 μV / K;

[0056] At 4 g bismuth telluride content, the Seebeck coefficient of the corresponding composite thermoelectric material is 180 μV / K;

[0057] At a bismuth telluride content of 10 g, the Seebeck coefficient of the corresponding composite thermoelectric material is 220 µV / K.

[0058] It can be seen that compared with Example 1, the comprehensive performance of Examples 2-5 is worse, but still has certain elastic compressibility and certain thermoelectric performance. In addition, the excess of p-type bismuth telluride powder was tested. After a large number of experiments, when the amount exceeded 10 g, excessive use would result in very low porosity and difficulty in dipping. Although part of the glue could be dipped, the sample was rigid and had almost no flexibility and compressibility. Therefore, in order to ensure the comprehensive performance, the mass of the polyurethane prepolymer 1 g is used as the benchmark in the present invention, and the corresponding mass of the bismuth telluride powder is preferably 5-8 g.

[0059] Embodiment 6-7

[0060] Two groups of embodiments are provided, respectively preparing elastically compressible bismuth telluride composite thermoelectric materials, and the specific methods are as follows:

[0061] The high temperature treatment temperature (560°C) in step (4) of Example 1 was changed to 400°C and 300°C respectively, and the remaining steps were the same as in Example 1.

[0062] According to the voltage-temperature difference fitting results, it can be seen that the Seebeck coefficient obtained under 400 ℃ high temperature treatment is about 191.42 μV / K ( Figure 8 A); Under 300 ℃ high temperature treatment, the Seebeck coefficient of the corresponding composite thermoelectric material is about 163.63 μV / K ( Figure 8 B), indicating that a lower treatment temperature will reduce the thermoelectric properties of the elastically compressible bismuth telluride composite thermoelectric material. The elastically compressible bismuth telluride composite thermoelectric material obtained by changing the high-temperature treatment temperature exhibits different thermoelectric properties. Lowering the high-temperature treatment temperature will gradually reduce the Seebeck coefficient. The high-temperature treatment is mainly to remove the polyurethane binder inside so that the bismuth tellurides maintain good contact, but too low a temperature will lead to incomplete removal of the polyurethane and reduced thermoelectric performance. Too high a temperature will cause the bismuth telluride to melt (melting point 573 ° C), so 560 ° C is preferably used as the upper limit temperature. Therefore, the preferred temperature range for high-temperature heat treatment in the present invention is 400-560 ° C.

[0063] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing an elastically compressible bismuth telluride composite thermoelectric material, characterized in that: The following steps are involved: 1) Mix bismuth telluride powder, graphene, pore former and polyurethane prepolymer evenly, and compact them in a mold for curing; Wherein: based on the mass of 1 g of polyurethane prepolymer, the mass of bismuth telluride powder is 0.5-10 g, the mass of pore-forming agent is 2-15 g, and the mass of graphene is 10-100 mg; the pore-forming agent is one or more of sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate; 2) soaking the sample obtained by curing in step 1) in water to remove sodium chloride, drying it, and then subjecting it to high temperature treatment at 400-560° C. in a protective atmosphere to remove polyurethane, thereby obtaining a porous sample; 3) The porous sample of step 2) is immersed in an Ecoflex solution diluted with n-hexane at a temperature of -10 to 5 °C so that Ecoflex completely fills the pores of the sample, and then the sample is taken out and placed in an oven for curing, thereby finally obtaining an elastically compressible bismuth telluride composite thermoelectric material.

2. The method for preparing the elastically compressible bismuth telluride composite thermoelectric material according to claim 1, characterized in that: The polyurethane type corresponding to the polyurethane prepolymer is one or a mixture of Clearflex PU95, Clearflex PU30, Clearflex PU60, and Clearflex PU200.

3. The method for preparing the elastically compressible bismuth telluride composite thermoelectric material according to claim 1, characterized in that: In step 1), based on the mass of the polyurethane prepolymer of 1 g, the corresponding mass of the bismuth telluride powder is 5-8 g.

4. The method for preparing the elastically compressible bismuth telluride composite thermoelectric material according to claim 1, characterized in that: In step 1), the curing temperature is 60-80°C and the curing time is 8-12 h.

5. The method for preparing the elastically compressible bismuth telluride composite thermoelectric material according to claim 1, characterized in that: In step 2), the sample is immersed in water to remove sodium chloride at a temperature of 80-100°C for 24-48 h; and / or, the drying temperature used for drying is 60-80°C for 2-4 h; and / or, the high temperature treatment time is 2-6 h.

6. The method for preparing the elastically compressible bismuth telluride composite thermoelectric material according to claim 1, characterized in that: In step 3), the porous sample is immersed in the Ecoflex solution diluted with n-hexane for 8-12 h.

7. The method for preparing the elastically compressible bismuth telluride composite thermoelectric material according to claim 1, characterized in that: In step 3), the curing temperature is 60-80°C and the curing time is 0.5-2 h.

8. The method for preparing the elastically compressible bismuth telluride composite thermoelectric material according to claim 1, characterized in that: In the Ecoflex solution, the mass ratio of n-hexane to Ecoflex prepolymer is 1:1-1:

2.

9. A bismuth telluride composite thermoelectric material, characterized in that: It is prepared by the method described in any one of claims 1 to 8.

10. Application of the bismuth telluride composite thermoelectric material according to claim 9 as a thermoelectric material in the fields of low-grade thermal energy collection, temperature monitoring, and wearable electronics.

Citation Information

Patent Citations

  • Inorganic thermoelectric material based flexible thermoelectric conversion device

    CN108649114A

  • Thermoelectric device based on high-elasticity compressible graphene / organic composite foam and preparation method thereof

    CN114005928A

  • Bismuth telluride-based alloy / carbon cloth thermoelectric composite material and preparation method thereof

    CN114464724A

  • Foam metal / bismuth telluride thermoelectric composite material

    CN114497338A

  • Thermal pattern sensor with pyroelectric capacity

    EP3492892A1